Effect of nitrogen and boron on available nutrients in sesame (Sesamum indicum L.) and harvested soil - Shamsuzzoha, Md; Jahan, Mst Afrose; Mostofa, Maruf; Afrose, Rashma; Sarker, Md Sadiquzzaman; Kundu, Partha Komol (Research in Agriculture Livestock and Fisheries, 2019)
A field experiment was carried out at the Soil Science research field of Sher-e-Bangla Agricultural University (SAU), Dhaka-1207, Bangladesh to study the nutrient uptake of sesame plant and available nutrient condition of soil after harvesting of sesame. Sesame variety BARI Til-3 was used as test crop. The experiment consisted of two factors. Factor A: Nitrogen levels (N0-3): N0: 0 kg N/ha (control), N1: 50 kg N/ha, N2: 60 kg N/ha, N3: 70 kg N/ha; Factor B: Boron levels (B0-2): B0: 0 kg B/ha (control), B1: 2 kg B/ha, B2: 3 kg B/ha. The experiment was carried out in two factors Randomized Complete Block Design (RCBD) with three replications. From the study, it was found that nutrient uptake of sesame plant and the nutrient concentration in post-harvested soil such as total N, available P, exchangeable K, available S and available B was increased with the increasing of nitrogen up to a certain level and boron supply. For the combined application of nitrogen and boron (60 kg N/ha and 3.0 kg B/ha) was found suitable to uptake maximum N, P, K, S and B by the sesame plant and to available the highest nutrient concentration in post-harvested soil. Res. Agric., Livest. Fish.6(2): 203-213, August 2019